Literacy practices, texts, and talk around texts: english language teaching developments in colombia - Valencia Giraldo, Silvia (Colombian Applied Linguistics Journal, 2006)
This paper seeks to provide a window into the complexity of classroom interaction in English language classes in public secondary schools in Colombia. It will show the relationship between what goes on in public schools and classrooms, the wider policy context, and recent reforms. Through a detailed analysis of data collected in two schools and the interaction that takes place between the two teachers and their students around and about texts, this artcicle provides insights into the specific nature of the literacy practices, the texts used, and the particular ways in which the teachers and learners made sense of these texts. It examines how the students are learning to read in English in these classes, and what the teachers understand by ‘doing reading’ and ‘reading comprehension’.